Tetranychus ludeni Zacher, 1913 (Tetranychidae) and Phytoseiulus macropilis (Banks, 1904) (Phytoseiidae) in apple trees grown in a greenhouse in southern Brazil: injuries and control - Rode, Priscila A.; Wurlitzer, Wesley B.; Ferla, Noeli J. (Entomological Communications, 2023)
This study reports the presence and injuries caused by Tetranychus ludeni Zacher, 1913 (Acari: Tetranychidae) on apple tree seedlings (Malus domestica Borkh: Rosaceae) in nurseries in southern Brazil. The ability of the predatory mite of Phytoseiulus macropilis (Banks, 1904) (Acari: Phytoseiidae) to control T. ludeni infestations in this environment was also evaluated. Tetranychus ludeni infestation was observed during routine monitoring at the Acarology Laboratory of the University of Vale do Taquari - Univates, Lajeado, Rio Grande do Sul. Injuries were observed on the leaves, with gradual growth linked to the population increase of T. ludeni. In the control seedlings, there was defoliation and weakening of the plant. Phytoseiulus macropilis released on infested plants controlled the populations of this phytophagous mite. Fifty specimens of P. macropilis were released in each seedling. Tetranychus ludeni caused injuries to apple seedlings, while P. macropilis proved to be efficient in controlling this phytophagous mite.